Inequality and creative destruction - Richard W. Blundell; Xavier Jaravel; Otto Toivanen (Institute for Fiscal Studies (IFS), 2022)
In this article we review recent evidence showing how market forces and policies shape the rate and direction of innovation, with various implications for inequality. First, we characterize several market mechanisms whereby higher rates of innovation lead to higher inequality. Second, we highlight channels whereby inequality acts as an impediment to innovation and growth. Third, we highlight policies that can help achieve better outcomes for both innovation and inequality. We show that two types of policies, which are not traditionally viewed as part of innovation policy, play a key role to achieve the goal of enhancing innovation while reducing inequality: education and competition policy.
Keywords: 330